Nurse Following Robot Using Colour Connected Components Algorithm - Hj Mohd, Mohd Norzali; Akhbar Ali, Akmal Zaki (Evolution in Electrical and Electronic Engineering, 2020)
Robot implementation in daily life from industrial to personal level showing repetitive work that required physical and consistency can be replaced by automation and machine. This project emphasizes on the process of developing nurse following robot as a personal robot to ease the everyday task of a nurse. The main function of this robot is to be able to bring any equipment or medicine for the nurse when attending each patient assigned. Hence, the main objective is to develop a nurse tracking and following robot with the application of colour connected components algorithm. The vision system used in this project is Pixy2 camera. The camera sensors system has its own simple controller that is able to detect, recognize, assign and memorize up to seven different targets or signature. The colour connected components algorithm use hue, saturation and light intensity with colour-based filtering algorithm to detect the assigned target also with region growing algorithm to know the size and distance of the target which is useful as a target following robot. The microcontroller used in this robot is Arduino UNO which has suitable processing power combine with Pixy2 for the tracking and mobility of the robot. Movement of robot is supported with an acrylic chassis with two DC motors. Controlling motion of the robot comes from the microcontroller and paired up with L298N Dual H-Bridge Motor Driver to interact with the DC motors. The robot is able to move with the coloured target either in straight or curve path with the limitation for indoor application and planar ground.